2018
DOI: 10.3390/f9090528
|View full text |Cite
|
Sign up to set email alerts
|

Drought Influence on Forest Plantations in Zululand, South Africa, Using MODIS Time Series and Climate Data

Abstract: South Africa has a long history of recurrent droughts that have adversely affected its economic performance. The recent 2015 drought has been declared the most serious in 26 years and impaired key agricultural sectors including the forestry sector. Research on the forests’ responses to drought is therefore essential for management planning and monitoring. The effects of the latest drought on the forests in South Africa have not been studied and are uncertain. The study reported here addresses this gap by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 65 publications
10
32
0
1
Order By: Relevance
“…These observations are consistent with a study by Xulu et al [10], who investigated the response of commercial forestry to the recent strong and broad El Niño event in a region which is 70 km south-east of the HiP. In their study, Xulu et al [10] reported a significant decline of NDVI values which corresponded to the 2014-2016 El Niño years [10]. Although the influence of the 2014-2016 El Niño in the HiP seems to be the strongest, it follows the same pattern as that reported by Anyamba et al [40] in their study of the influence of both El Niño and La Niña in the vegetation status over eastern and southern Africa.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…These observations are consistent with a study by Xulu et al [10], who investigated the response of commercial forestry to the recent strong and broad El Niño event in a region which is 70 km south-east of the HiP. In their study, Xulu et al [10] reported a significant decline of NDVI values which corresponded to the 2014-2016 El Niño years [10]. Although the influence of the 2014-2016 El Niño in the HiP seems to be the strongest, it follows the same pattern as that reported by Anyamba et al [40] in their study of the influence of both El Niño and La Niña in the vegetation status over eastern and southern Africa.…”
Section: Resultssupporting
confidence: 94%
“…There is an expected resemblance between the NDVI and EVI observations in both the monthly mean time series and the smooth trend, with a clear indication of the effect of the 2014-2016 drought period. These observations are consistent with a study by Xulu et al [10], who investigated the response of commercial forestry to the recent strong and broad El Niño event in a region which is 70 km south-east of the HiP. In their study, Xulu et al [10] reported a significant decline of NDVI values which corresponded to the 2014-2016 El Niño years [10].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations